Enhanced amylase production by a Bacillus subtilis strain under blue light-emitting diodes. Issue 2 (7th February 2019) - Elumalai, Punniyakotti; Lim, Jeong-Muk; Park, Yool-Jin; Cho, Min; Shea, Patrick J.; Oh, Byung-Taek
Abstract: A chemotrophic, aerobic bacterial strain, Bacillus subtilis B2, was used to produce amylase by submerged fermentation under different light sources. SDS-PAGE indicated that the 55 kDa enzyme belonged to the α-amylase group. B2 was incubated in basal media with 1% soluble starch (pH 7.0) under blue, green, red, and white light-emitting diodes (LEDs), and white fluorescent light. Fermentation under blue LEDs maximized amylase production (180.59 ± 1.6 U/mL at 24 h). Production at 48 h increased to 310.56 ± 1.6 U/mL with 5% glucose as a simple carbon source and to 300.51 ± 1.7 U/mL with 5% groundnut oil cake as an agricultural waste substrate. Activity and stability of the amylase were greatest at pH 7.0 and 45–55 °C. Na +, Ca 2+, Mg 2+, Co 2+, Ba 2+, and K + increased activity, while Ni 2+, Hg 2+, Mn 2+, Cu 2+, Fe 3+, and Zn 2+ inhibited activity. EDTA, PMSF and DTNB reduced activity by 50% or more, while tetrafluoroethylene and 1, 10-phenanthroline reduced activity by 30%. The amylase was highly tolerant of the surfactants, compatible with organic solvents, oxidizing agents and the reducing agents reduced activity. These properties suggest utility of amylase produced by B. subtilis B2 under blue LED-mediated fermentation for industrial applications.